Izkušnje študentov zdravstvene nege z izobraževanjem na daljavo v času prvega vala epidemije covida-19 - Plesec, Špela (Obzornik zdravstvene nege, 2023)
Introduction: The declaration of the COVID-19 epidemic also resulted in urgent changes in the education process. The objective of this study was to identify the experiences of nursing students with the adapted educational process during the first wave of the epidemic.Methods: A qualitative method was used. Data were collected through in-depth semi-structured interviews in June and July 2020. Thirteen nursing students were included in the convenient sample. The text was analyzed using inductive thematic analysis.Results: We identified the following themes and subthemes: advantages of distance education (better conditions for studying, time flexibility, psychological factors, teaching methods, support and a more personal relationship with lecturers, cost-effectiveness, and more time for studying and leisure activities), weaknesses of distance education (changed teaching methods, psychological factors, inaccessibility of study literature, inadequate infrastructure and poor study conditions, lack of personal contact and social support, poor digital literacy of lecturers and difficulties with organization, communication and information), applied teaching methods and digital tools, and suggestions for improvement.Discussion and conclusion: Nursing students stated both positive and negative experiences with the adapted education process. For a holistic picture of the education process during the epidemic, the experience of lecturers should be examined also. The results of the study may serve as incentive in the choice of teaching methods and digital tools and as a guideline for lecturers and the management in the planning of modern and innovative forms of education in the field of nursing.
Keywords: coronavirus; doživljanje; experiences; koronavirus; online education; spletno izobraževanje; tematska analiza; thematic analysis